Pripojitev s povečanim finančnim vzvodom - Plavšak, Nina (Podjetje in delo, 2015)
The author discusses legal and financial effects of merger by leveraged buyout. A characteristic of this type of merger is that a special purpose vehicle (SPV) is established for a sole purpose of debt financing the acquisition of shares of the target company. By merging the SPV with the target company obligation (debt) assumed by the SPV for acquisition of shares of the target company is transferred to the target company. Merger by leveraged buyout is a corporate action that the Slovenian Companies Act (ZGD-1) regulates by defining additional prerequisites (consents of creditors) in order to protect interest of the creditors of both companies. Therefore, this type of merger is allowed (legal) and is not in contradiction with prohibitions to finance acquisition of companies' own shares, regulated in Article 248 of the Companies Act.
Keywords: delnice; financiranje; gospodarske družbe; združevanje